Personality traits and career adaptability in adolescents: The mediating role of core self-evaluations - Šimunović Mara (Psihologija)
The aim of this study was to extend previous findings on antecedents of career adaptability in adolescence. Drawing on career construction theory and the distal-proximal theory of motivation, we investigated the mediating role of core self-evaluations in the relationship between basic personality traits and career adaptability in adolescence. The study included 1793 Croatian high-school students from 18 high schools who attended first to third grade. Path analysis revealed that adolescents’ higher core self-evaluations partially accounted for the predictive effects of extraversion and conscientiousness on their career adaptability. Conscientiousness and extraversion were positively related to core self-evaluations, which, in turn, were related to higher career adaptability. There was also a very small but significant indirect effect of students’ openness to experience on their career adaptability via core self-evaluations. Conscientiousness, extraversion, and openness to experience were directly and positively related to career adaptability. Theoretical and practical implications of the findings are discussed.